Pemilihan Metode Pembelajaran Pendidikan Agama Islam yang Efektif di Kampus Akademi Farmasi Dwi Farma Bukittinggi - Zul Efendi (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This study examines the strategy for selecting Islamic Religious Education (PAI) teaching methods at the Dwi Farma Pharmacy Academy in Bukittinggi. Using a qualitative approach with a case study method, the research involved 20 participants including PAI lecturers, students, and academy leaders. Results show that method selection is influenced by pharmacy students' characteristics, the need to contextualize PAI materials with pharmaceutical ethics, technology availability, and diversity in students' religious knowledge. Interactive and problem-based methods prove more effective. Main challenges include time constraints and learning technology optimization. The research recommends developing integrated modules, enhancing lecturers' technology competence, implementing peer mentoring, and fostering collaboration between PAI and pharmacy lecturers. This study contributes to the development of effective PAI learning strategies in pharmacy higher education institutions.